Liesegang rings as origin of enamel symmetrical patterns - Rodríguez-Blanco, Mario; Delgado-Mejía, Edgar (Revista Facultad de Odontología Universidad de Antioquia, 2015)
Introduction: teeth contain various visible structures that have repeating shapes and symmetrical patterns such as prisms, crests, enamel spindles, Hunter-Schreger bands, and Retzius incremental lines. On the other hand, Liesegang rings, studied and applied for over a hundred years by geologists and other specialists, are incremental repetitive symmetrical bands found in natural minerals which are similar to those observed in tooth enamel. This article aims to review the widely known processes of formation of Liesegang rings in nature and relate them with dentin mineralization and the conformation of their characteristic anatomy. Methods: to this end, a bibliographic review was conducted, restricted to the 1970-2013 period, in the Science Direct, Springer, Medline, and Pubmed databases, finally selecting 51 references with original information or relevant data on the subject. Results and conclusions: a detailed analysis of the processes of formation of these rings and the similarity of rocky and dental minerals lead to think that the processes developed in rocks and hard dental tissues would be the same.